Dietary habits and risk of urothelial cancer death in a large-scale cohort study (JACC Study) in Japan - Sakauchi, F; Mori, M; Washio, M; Watanabe, Y; Ozasa, K; Hayashi, K; Miki, T; Nakao, M; Mikami, K; Ito, Y (Nutrition and cancer, 2004)
In the present study, the associations of dietary habits with the risk of urothelial cancer death were evaluated taking into consideration sex, age, and smoking habits. The Japan Collaborative Cohort Study was established in 1988-1990 and consisted of 47,997 men and 66,520 women observed until the end of 1999. A self-administered food-frequency questionnaire was used as a baseline survey. Hazard ratios for dietary factors were calculated by Cox's proportional hazards model. During the observation period, 63 men and 25 women died of urothelial cancer. Increasing age, male gender, and history of smoking were all significantly associated with increased risk of urothelial cancer death. A high intake of milk and fruits other than oranges reduced the risk significantly and dose dependently, in particular among subjects with smoking history. However, consumption of butter and yogurt had no associations with the risk. Intakes of cabbage, lettuce, green leafy vegetables, carrots, squash, tomatoes, and oranges were not significantly associated with the risk. It was suggested that urothelial cancer death could be potentially preventable by smoking cessation and regular intake of milk and fruit.